Pengaruh Berbagai Bahan Organik dan Pupuk Kalium Terhadap Pertumbuhan dan Produksi Tanaman Melon (Cucumis melo L) - Ramadhan, Rizky; Putra, Irwan Agusnu; Kurniawan, Dedi (CV. Eduartpia Publisher, 2024)
The increasing public demand for melons has encouraged the cultivation sector to make improvements by providing inorganic materials accompanied by providing organic materials so that the quality of the soil and the quality of the melons also improves. The aim of this research is to analyze the effect of various organic materials and potassium treatments on the growth and production of melon plants. This research was carried out in Diski, Sunggal sub-district from June to August 2023. The research design used in this study was a Randomized Group Factorial Design (RAK) which consisted of two factors, the first factor was various organic materials O1: rice husk, O2: coconut belt, O3: water hyacinth. Factor 2. KCL K0: 0 g/plant, K1: 9.0 g/plant, K2: 18 g/plant. The parameters observed were plant length (cm), number of leaves (strands), fruit weight (gr), fruit diameter (cm), fruit thickness (cm). In this study, the treatment of various organic materials had a significant effect on plant height aged 4 to 7 WAP, number of leaves aged 3 and 7 WAP, plant fruit weight and fruit thickness, while potassium treatment had a significant effect on the number of leaves aged 6 WAP, plant fruit weight, and fruit diameter. Treatment interactions had a significant effect on the parameters of plant height aged 3 and 4 WAP